Analysis and Development of School Management Information System at SMA Insan Madani Palopo - Malik, Abdul; Batupadang, Michael; Taufiq; Kurniawan, Fahmi; Ma’arif, Syamsul (Cattleya Darmaya Fortuna, 2024)
This study aims to analyze and develop a school management information system at SMA Insan Madani Palopo. This system is expected to improve efficiency in the management of academic administration, finance, and school staffing. The method used in this research is a qualitative method with a case study approach. Data was collected through interviews, observations, and document studies. The research results show that the developed management information system can enhance efficiency in managing student, teacher, and school activity data. The implementation of a web-based system allows for easier and faster access for all stakeholders